Efeitos da apresentação intermitente de consequências culturais sobre contingências comportamentais entrelaçadas e seus produtos agregados - VICHI, Christian (Universidade Federal do Pará, 2018)
The social behavior of an individual can be interlocked with the others and give rise to interlocking behavioral contingencies (IBCs), whose coordination can generate aggregate products (APs) with the function of cultural consequences (CCs). Such elements may take part in a metacontingency, thus configuring the selection process at the cultural level. In complex cultural practices, a receiving system (RS) can perform the function of releasing CCs. Experiments have shown that CCs can select and keep the IBCs and their APs. Other studies have suggested the possibility of maintain and even install the IBCs and their APs through intermittent CCs on VR2, and extinguish them. The present study investigated the possibility of maintain the IBCs and their APs by applying intermittent CCs on a CRF, FR2, VR3, FR3 and VR3 schedule and the effect of the subsequent suspension of CCs. The study included 93 participants from higher education, appointed to one of five experiments. Each group had one to three participants at the same moment, and each participant chose a line in a 10x10 matrix with numbered rows of five different colors and alphabetically named columns. After each participant chooses a row, the experimenter chose a column whose intersection cell could contain a black circle that gives a token worth 10 cents for the participant. The same procedure was then applied to the other participants. In some phases, when the color of the line chosen by each participant differed from the others it was applied a CC on the group, in the form of stickers exchangeable for donation school supplies. The groups that composed the experiment were exposed to different metacontingencies: CRF, FR2, VR2, VR3 and FR3, and all were exposed to a final extinction. All groups began with one participant on the selection phase and gradually the complexity was increased adding participants and changing metacontingencies. At the end of the study, participants answered a brief questionnaire. The results corroborated the data found in literature, suggesting the selection of IBCs and their PAs and their maintenance through the application of intermittent CCs in schedules of FR2, VR2, VR3 and FR3. The study was unable to determine whether there were differences in resistance to extinction of IBCs comparing the various tested schedules, because this was not clearly obtained. However, an analysis of cultural variability suggests the beginning of an extinction process due to increased variability of the IBCs along extinction. It also suggests IBCs should conform to analogous principles to those observed in operant variability. The verbal descriptions of the contingencies of reinforcement were very common among participants, but the descriptions of metacontingencies occurred with lower frequency, especially those exposed to Extinction and VR3.